AN ANALYSIS ON THE CAUSE OF STUDENTS' SPEAKING ANXIETY IN EFL CLASSROOM - Nurilahi, Reski; Suhartono, Luwandi (Journal of English Education Program, 2022)
Speaking is one of four skills that are deemed to be important. In EFL Classroom, the students often suffer from English speaking anxiety. The purpose of this research was to discover the level of students"™ speaking anxiety and the causes behind it. Descriptive qualitative was used to investigate this research. This research was conducted on the twelfth-grade students of XII-IIS 2 of MAS Ushuluddin Singkawang. To obtain the data, observation and two questionnaires were applied. The questionnaires being used were Foreign Language Classroom Anxiety Scale and the Factors Causing Students"™ Speaking Anxiety Questionnaire. To analyze the obtained data, data condensation, data display, and drawing conclusions were applied. The result revealed that 97% of the students experienced high to moderate levels of speaking anxiety. The causes of students"™ speaking anxiety were mainly the psychological factors such as; afraid of being laughed at; afraid of not having enough time to prepare; feeling inferior; nervous or shy; anxious when performing alone; afraid of the speaking test; terrified that other students will not understand; afraid of making mistakes; afraid of teacher"™s immediate correction; students"™ beliefs about speaking English; frightened of teacher"™s and peer"™s evaluation, and formal class situation. In conclusion, more than two-thirds of the students experienced high to moderate levels of speaking anxiety and 12 factors were found to be the causes behind the speaking anxiety in EFL classrooms.